2000
DOI: 10.1523/jneurosci.20-18-07052.2000
|View full text |Cite
|
Sign up to set email alerts
|

Deficit of Striatal Parvalbumin-Reactive GABAergic Interneurons and Decreased Basal Ganglia Output in a Genetic Rodent Model of Idiopathic Paroxysmal Dystonia

Abstract: The underlying mechanisms of various types of hereditary dystonia, a common movement disorder, are still unknown. Recent findings in a genetic model of a type of paroxysmal dystonia, the dt sz mutant hamster, pointed to striatal dysfunctions. In the present study, immunhistochemical experiments demonstrated a marked decrease in the number and density of parvalbuminimmunoreactive GABAergic interneurons in all striatal subregions of mutant hamsters. To examine the functional relevance of the reduction of these i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
121
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 144 publications
(144 citation statements)
references
References 41 publications
21
121
2
Order By: Relevance
“…The dt sz hamster phenotype shares many features with TS, including facial contortions, co-contractions of opposing muscle groups (33), and a similar age-dependent time course (34). Remarkably, the dt sz hamster also has a strikingly similar reduction in striatal PVϩ interneuron number (41% decrease, compared with 54% decrease in Cd of TS) (35). These emerging lines of data strongly support a role for striatal PVϩ interneuron deficit in TS and other hyperkinetic disorders.…”
Section: Discussionmentioning
confidence: 74%
“…The dt sz hamster phenotype shares many features with TS, including facial contortions, co-contractions of opposing muscle groups (33), and a similar age-dependent time course (34). Remarkably, the dt sz hamster also has a strikingly similar reduction in striatal PVϩ interneuron number (41% decrease, compared with 54% decrease in Cd of TS) (35). These emerging lines of data strongly support a role for striatal PVϩ interneuron deficit in TS and other hyperkinetic disorders.…”
Section: Discussionmentioning
confidence: 74%
“…For example, the uniform suppression of FSI firing by eticlopride indicates that the therapeutic benefits of D2 antagonists in Tourette syndrome are unlikely to derive from increasing FSI firing to compensate for their reduced number (Kalanithi et al, 2005). Rather, given that a deficit in striatal FSIs is found in a rodent model of paroxysmal dystonia (Gernert et al, 2000), and that dystonias and dyskinesias are produced by local GABA blockade in striatum (for example, Yoshida et al, 1991;Worbe et al, 2009), FSI suppression is a strong candidate mechanism for the adverse behavioral effects of antipsychotic treatment (which include dystonias, dyskinesias, and akathesia; Hyman et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Recent rodent studies have reported that activity in dorsal striatum is correlated with movement velocity and acceleration (Costa et al, 2004;Yeshenko et al, 2004), however, none of these studies have attempted to classify the recorded neurons into distinct cell-types. Circumstantial evidence links FSIs to movement abnormalities: a reduced number of FSIs has been observed in human Tourette syndrome (Kalanithi et al, 2005) and in animal models of dystonia (Gernert et al, 2000); moreover, selective inhibition of FSIs was reported to elicit robust dystonia-like impairments (Gittis et al, 2011). Interestingly, locomotor-correlated activity of FSIs was shown under the influence of psychomotor stimulants and antipsychotic drugs modulating FSI activation .…”
Section: Neuronal Identification and Recording Biasmentioning
confidence: 99%